Knitting Legislative Meaning: A Review of Disability Education Policy in the Law on the National Education System and Disabilities - Zamroni Abdussamad; Anna Triningsih; Mohamad Hidayat Muhtar; Arief Fahmi Lubis; Wiwik Widyo Widjajanti; Dede Agus (Faculty of Law, Universitas Pekalongan, 2023)
This study set out to address the question,